2018
DOI: 10.1080/14767058.2018.1450864
|View full text |Cite
|
Sign up to set email alerts
|

Breast milk oligosaccharides: effects of 2′-fucosyllactose and 6′-sialyllactose on the adhesion of Escherichia coli and Salmonella fyris to Caco-2 cells

Abstract: Our results suggest that the supplementation in infant formulas of 2'-fucosyllactose and 6'-sialyllactose, actually commercially available and absent in cow milk, could play positive effects in artificially fed infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 14 publications
1
39
0
2
Order By: Relevance
“…However, it is significant in this regard that Coppa et al (34) found species differences between E. coli, Vibrio cholerae and S. fyris in experiments using HMO and (like us) Caco-2 cells. Whilst some recent studies have reported that oligosaccharides from human, cows' and goats' milk (55,56) are effective in inhibiting the adhesion of E. coli to gut cells, these experiments were conducted using much higher concentrations of oligosaccharides than we used in our study, suggesting the possibility of a dose-dependent effect. In our study, GOS was at least equally as effective as goat milk oligosaccharides in preventing the adhesion of E. coli and S. typhimurium (by 52•4 and 35 %, respectively, compared with the negative control; see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…However, it is significant in this regard that Coppa et al (34) found species differences between E. coli, Vibrio cholerae and S. fyris in experiments using HMO and (like us) Caco-2 cells. Whilst some recent studies have reported that oligosaccharides from human, cows' and goats' milk (55,56) are effective in inhibiting the adhesion of E. coli to gut cells, these experiments were conducted using much higher concentrations of oligosaccharides than we used in our study, suggesting the possibility of a dose-dependent effect. In our study, GOS was at least equally as effective as goat milk oligosaccharides in preventing the adhesion of E. coli and S. typhimurium (by 52•4 and 35 %, respectively, compared with the negative control; see Fig.…”
Section: Discussionmentioning
confidence: 94%
“…In this study, the significantly higher percentage of fucosylated structures in human milk, compared to that in goat and bovine milk, may explain the overall antipathogenic potency of the three milk types: HMN >GMN >BMN. Sialylation has also been reported to be associated with the antimicrobial activity of oligosaccharides (Barboza et al., 2012; Facinelli et al., 2019; Martin‐Sosa et al., 2002). The sialylation levels in HMN and BMN are similar; although the level of sialylation in GMN is lower than in BMN and fucosylation levels of these two samples are similar, the higher levels of other types of sugars may compensate the difference and make BMN better in pathogen inhibition.…”
Section: Resultsmentioning
confidence: 99%
“…Currently, over 150 different HMO structures have been identified in humans and there seems to be considerable heterogeneity in the biological effects. For instance, HMOs that have sialyated or fucosylated side chains decrease pathogen burden, decrease NEC, and the addition of sialic acids to galacto‐oligosaccharides seem to confer NEC‐protection . Individual HMOs also seem to impart structure‐specific effects: for example, 2‐fucosyllactose (2’FL) dampens the activity of TLR‐4 signaling—a pathway involved in expression of PDI—whereas 6’‐sialyllactose (6’SL) can decrease the adherence of Escherichia coli .…”
Section: Discussionmentioning
confidence: 99%